Resting state connectivity of the bed nucleus of the stria terminalis at ultra‐high field. Issue 10 (14th July 2015) - Torrisi, Salvatore; O'Connell, Katherine; Davis, Andrew; Reynolds, Richard; Balderston, Nicholas; Fudge, Julie L.; Grillon, Christian; Ernst, Monique
Abstract The bed nucleus of the stria terminalis (BNST), a portion of the "extended amygdala, " is implicated in the pathophysiology of anxiety and addiction disorders. Its small size and connection to other small regions prevents standard imaging techniques from easily capturing it and its connectivity with confidence. Seed‐based resting state functional connectivity is an established method for mapping functional connections across the brain from a region of interest. We, therefore, mapped the BNST resting state network with high spatial resolution using 7 Tesla fMRI, demonstrating the in vivo reproduction of many human BNST connections previously described only in animal research. We identify strong BNST functional connectivity in amygdala, hippocampus and thalamic subregions, caudate, periaqueductal gray, hypothalamus, and cortical areas such as the medial PFC and precuneus. This work, which demonstrates the power of ultra‐high field for mapping functional connections in the human, is an important step toward elucidating cortical and subcortical regions and subregions of the BNST network. Hum Brain Mapp 36:4076–4088, 2015. © 2015 Wiley Periodicals, Inc.